Morphological Transformation Network of Nanoparticles via DFT Simulations - Laranjeira, J. A. S. [UNESP]; Fabris, G. S. L. [UNESP]; Ferrer, M. M.; Albuquerque, A. R.; Sambrano, J. R. [UNESP] (Amer Chemical Soc, 2020)
The development and advancement of nanomaterials engineering have become essential points in the goal of designing new materials with applications of particular interest. Therefore, computer simulations at the atomic level have the upper hand in being able to predict the behavior, shapes, and properties of materials. In this sense, a new theoretical methodology was developed to run a complete analysis of the morphological transformation network of nanoparticles through a roadmap, in addition to establishing a direct relationship between computational models and real particles, beginning with the surface characteristics. This procedure includes the assessment of the electronic characteristics of nanoparticles as a function of the exposed surface area contribution of each nanoparticle, and it also unravels essential questions regarding the morphological contribution to the properties of this system. For the application of this methodology, the transition-metal molybdate CdMoO4 was chosen as the probe system. A computational routine able to estimate the electronic properties of nanoparticles according to the different nanoparticle morphologies was also performed.